MACROECONOMIC DETERMINANTS OF CAPITAL MARKET PERFORMANCE IN AN OPEN ECONOMY: EVIDENCE FROM NIGERIA - Yinka Ibrahim AGBEYINKA (International Journal of Social and Educational Innovation)
Global market dynamics, investor behavior, regulatory frameworks, technological developments, and macroeconomic indicators are just a few of the many variables that influence capital market performance. The study looked at the factors that affect Nigeria's capital market performance. For this study, a yearly time-series data set from 2001 to 2022 was obtained from the Securities Exchange Commission (SEC) and the Central Bank of Nigeria (CBN). To estimate the model's parameters, data was subjected to linear regression analysis. The findings demonstrated that Nigeria's economic market capitalization is greatly increased by business earnings. Macroeconomic indicators have a major positive impact on Nigeria's economic market capitalization. Market capitalization is negatively impacted by exchange rates. This indicates that a rise in the exchange rate will result in a decline in market capitalization, while foreign direct investment has a favorable effect on Nigerian market capitalization. Therefore, the study suggested that the government enact laws and offer incentives that promote businesses' expansion and financial success. Tax incentives, better financing availability, and business-friendly laws can all help achieve this. This study suggests that the government should use monetary policy tools and foreign exchange reserves to mitigate excessive exchange rate volatility, control inflation, maintain low interest rates, and encourage sustainable economic growth in order to ensure stable macroeconomic conditions. Additionally, the government should develop policies that attract foreign direct investment, such as lowering bureaucratic barriers, guaranteeing political stability, and offering alluring investment incentives.